Ekoinnowacje w agrobiznesie jako czynnik konkurencyjności - Ziółkowski, Bożydar (Ecoinnovativeness in Agribusiness as Competitiveness Factor, 2006)
The aim of this paper is to present a new paradigm within the area of agribusiness competitiveness. There is displayed - not used so far - a new way of connection e.i. between agribusiness and ecoinnovation. The given examples of benefits which may be achieved thanks to the introduction of ecoinnovation have both an environmental, social and economic character.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 553-558